TEACHERS' VOLITION, INSTRUCTION AND CORRECTION STRATEGIES FOR TEACHING STUDENTS' WITH BEHAVIOURAL PROBLEMS IN GENDER- SPECIFIC SECONDARY SCHOOLS IN ANAMBRA STATE- NIGERIA - Nkechi Uzochukwu OKEKE; Ngozi Elizabeth EZENWOSU; Adeline NNE ANYANWU (Social Sciences and Education Research Review)
Teachers' volition, relevant instruction and correction strategies are vital factors in capturing students' interest, attention, commitment and positive emotions in a learning situation which of course will allow them less time to engage in behavioural problems. The study adopted descriptive research design to investigate teachers' volition, instruction and correction strategies for teaching students' with behavioural problems in gender-specific secondary schools in Anambra state-Nigeria. Seven research questions guided the study. The population comprised all the 1,825 teachers in male secondary schools in Anambra state. A sample of 80 teachers was randomly selected from the schools using simple random sampling technique. A researcher-developed instrument named “Teachers' Volition, Instruction and Correction Strategies" (TVICS) was used for data collection. The instrument was validated by specialists in Education. The reliability of the instrument was determined using Cronbach alpha method and an alpha coefficient of 0.78 was obtained. The research questions were answered using frequencies, percentages and statistical weighted mean. The result of the study revealed that most teachers' lack volition to teach students' with behavioural problems. Also the instruction and correction strategies employed by majority of the teachers do not trigger intrinsic motivation and positive emotions of the students' which are vital for transformation of behavioural problems. Based on the findings, the researchers' recommended the use of instructional strategies like co-operative learning, games/simulations, project method, field trips/excursions, role playing as well as correction strategies like premack principle, praise and reinforcement among others.